Analysis of profitability, return on investment, and liquidity ratios on the value of LQ45 companies during the 2017-2021 period - Chris Holan Aditia Hutagalung; Enjelina Tambunan; Chichi Kembaren; Yeni Lastari Simbolon; Maya Sabirina Panggabean; Maduma Sari Sagala (Journal of Economics and Business Letters, 2023)
A company has primary reasons to start a business, namely to maximize profits and maximize the value of the company. A high company value indicates good company performance, thus attracting investors to invest in the company. This research was conducted with the aim to test and analyze how the profitability ratio, profitability, and liquidity affect the value of LQ45 companies listed on the Indonesia Stock Exchange for the period 2017-2021. The data used in this research is quantitative data, the population of this research is the LQ45 companies listed on the IDX for the period 2017 -2021, amounting to 67 companies, with a sample of 9 companies sought using purposive sampling technique, meaning using a technique with certain criteria. The t-test results show that the significance value is 0.75. It can be seen that the profitability value is greater than the significance level of 0.05, which means that this profitability value significantly statistically affects the company's value.